Pemanfaatan Ecoenzyme melalui Pembuatan Sabun Cuci Piring Limbah Mawar Guna Meningkatkan Nilai Tambah Mawar di Desa Mriyan, Boyolali - Tsany, Fadhlan Muhammad; Mustika, Junita Andika; Billa, Bunga Salsha; Rosyida, Ibna Amalia; Listianti, Defina; Fairuzi, Sabilatussilmi; Balya, Muhammad Syihabuddin; Alghaniiyyu, M Rizqi; Hardjanto, Arini (Jurnal Pusat Inovasi Masyarakat, 2024)
The Community Service Program (KKN) in Mriyan Village aimed to transform rose waste into value-added products, specifically ecoenzyme-based dish soap, while raising community awareness about organic waste management. The program involved the local women’s group or Pemberdayaan dan Kesehatan Keluarga (PKK) as the main participants in training on ecoenzyme production and its derivative products. The Implementation strategies included socialization, practical instruction, and assessment using pre- and post-tests to gauge participants' increased understanding. The results showed that participants successfully mastered the techniques of producing ecoenzyme and dish soap, as evidenced by significant improvements in post-test scores. Additionally, the high enthusiasm of the participants indicated the effectiveness of the socialization methods employed. This program not only enhanced the community's skills in waste management but also positively affected the local economy through the possible growth of ecoenzyme-based businesses. The conclusion drawn from this activity is that utilizing rose waste to produce ecoenzyme holds promising prospects for sustainable implementation, provided the local administration and the community work closely together, as well as product diversification.